Creating new knowledge based on the ecological teaching material in Indonesian language education - Abdurahman Adisaputera; M Oky Fardian Gafari; Wahyu Wiji Astuti; Muhammad Hafidz Assalam (JOALL (Journal of Applied Linguistics and Literature), 2023)
This article is based on research and development entitled “The Development of Digital Teaching Language in Indonesian Language Subjects based on Malay Ecology”. In general, ecology-based research is not a new discovery. However, this research provides a new dimension related to the concept of Freedom to Learn. The concept of ecology has a direction for adapting education to the needs of students, as with independent learning which wants education to go according to the needs and characteristics of different students. Freedom to learn brings the same passion to concretize ecology-based education. The research data shows that 59% of students in SMA 1 Limapuluh, SMA 1 Asahan, SMA 1 Tanjungbalai and SMK 4 Tanjungbalai, assess that the Indonesian language subject matter teaching materials that have been used so far do not contain ecological content related to nature, the environment and their own culture. The teacher explained that this had an impact on 1) the difficulty of the teacher in providing examples, 2) the difficulty of students understanding the material and 3) the material being incompatible with the real life of students. Of course this is a problem. This research resulted in a conceptual understanding that the teacher's difficulty in providing examples of learning and the teacher's difficulty in relating material to the real life of students is due to the unfulfilled ecological dimension. This ecological dimension can be fulfilled by linking environmental values into materials, tests and assessments. The solution that can be offered from this article is to present Indonesian language subject materials based on local ecology. Also, as a concretization of "Merdeka Belajar" (Freedom to Learn) Program in the pandemic era, there must be a Learning Management System (LMS) developed by schools to support the learning process so that teachers and students have the freedom to create Indonesian language learning that is relevant to the needs of students.